A responsabilidade penal do compliance officer sob a ótica brasileira - Guimarães, César Caputo (2020)
The purpose of this paper is to analyze the criminal responsibility of the compliance officer, subject not well developed in the Brazilian scenario. Therefore, it was firstly analyzed the internationalization of Criminal Law, given the transcendence of territorial limits in business crimes, especially regarding money laundering. Then, the concept and scope of compliance and how integrity programs are embedded in Brazilian economic criminal law is summarized. The first topic concern the functions, base and criminal issues in general matters, getting to the concept of ‘corporative panoptic’, referring to the corporate control of the criminal matters. Subsequently, a dogmatic criminal analysis of the compliance officer is made, addressing issues, such as improper omissive criminal offence, objective imputation and guarantor’s position. In addition it will be analyzed the problems that a compliance officer has to face in its function. Finally, some concrete cases of the Brazilian and international courts are selected, relating them to the dogmatic concepts previously exposed.